ENHANCING SUICIDE RISK ASSESSMENT WITH A BRIEF VERSION OF THE REASONS FOR LIVING SCALE-OLDER ADULT VERSION (RFL-OA). (16th November 2018) - Wadhwa, S; Heisel, M
Abstract: Older adults have high rates of suicide and employ highly lethal means of self-harm (WHO, 2014). The aging of the population necessitates tools that quickly identify suicide risk and resiliency processes (Heisel & Duberstein, 2016). Linehan and colleagues (1983) initially identified Reasons for Living (RFL) as an adaptive psychological construct potentially preventive of suicide thoughts and behavior. Age-specific RFL scales have since been developed, including for older adults. The purpose of the present study was to develop and evaluate a brief version of the Reasons for Living Scale-Older Adults version (RFL-OA; Edelstein et al., 2009) for use in clinical and research contexts. A series of secondary analyses was conducted of a combined dataset (N=204) derived from three studies of late-life suicide ideation (Heisel & Flett, 2006; Heisel et al., 2015; Heisel, Neufeld, & Flett, 2016). We specifically assessed RFL-OA item distributions, and their contribution to internal consistency, construct validity, and social desirability. Thirty RFL-OA items were significantly associated with lifetime history of suicide attempt. Of these, 13 items were also associated with current suicide ideation. No item was highly correlated with social desirability. Findings supported the internal consistency, test-retest reliability, and construct and criterion validity of this abbreviated RFL scale. This study's findings support the reliability and validity of a 13- item Reasons for Living-Suicide Risk scale (RFL-SR) for use with clinical and/or community-residing samples of older adults. These findings suggest promise for this abbreviated measure in assessing a psychological construct potentially protective against later-life suicide risk.